La asociación estratégica Unión Europea-América Latina: ¿unas relaciones birregionales con geometría variable? - Grabendorff, Wolf (2013)
Since the proclamation of the strategic partnership between the EU and LAC 15 years ago the international system has changed dramatically with clear impact upon the biregional relations. It is therefore essential to evaluate the change in the mutual perceptions of both regions and take into account the new geopolitical context including the loss of influence of the USA and the rise of Asia especially China in the region. The strategic partnership has so far neither produced a convergence of interests nor a compatibility of acceptable norms between both regions. The EU has additionally lost its attractiveness as a “model of integration” in a region where the difference of development models has contributed to an increasing heterogeneity. It has become therefore necessary to adapt the birregional relations to the realities of the XXI century in applying a variable geometry.